2001
DOI: 10.1093/humrep/16.2.293
|View full text |Cite
|
Sign up to set email alerts
|

Co-incubation of human spermatozoa with Chlamydia trachomatis serovar E causes premature sperm death

Abstract: The aim of this work was to investigate the effect of elementary bodies (EB) of Chlamydia trachomatis serovars E and LGV on sperm motility, viability and acrosomal status. Highly motile preparations of spermatozoa from normozoospermic patients were co-incubated for 6 h with 0.54x10(6) EB per ml. At 1, 3 and 6 h of incubation, sperm motility was determined by computer-assisted semen analysis (CASA) and the proportion of dead cells determined by the hypo-osmotic swelling (HOS) test. Acrosomal status was also exa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
3

Year Published

2004
2004
2016
2016

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(73 citation statements)
references
References 27 publications
4
65
1
3
Order By: Relevance
“…LCS was associated with decreased sperm count, % normal forms and fructose concentration, a measure of seminal vesicle function. Thus, the present study confirms and extends earlier reports that STIs and LCS are associated with poor semen quality (7,13,45,48,49,51,64,65,70,(77)(78)(79)(80)(81)(82).…”
Section: Discussionsupporting
confidence: 92%
“…LCS was associated with decreased sperm count, % normal forms and fructose concentration, a measure of seminal vesicle function. Thus, the present study confirms and extends earlier reports that STIs and LCS are associated with poor semen quality (7,13,45,48,49,51,64,65,70,(77)(78)(79)(80)(81)(82).…”
Section: Discussionsupporting
confidence: 92%
“…The dead S. aureus neither adhered to spermatozoa nor induced any changes in the morphology (Figure 3b) which might be the reason of causing no immobilization of the spermatozoa. In an earlier study, Hosseinzadeh et al (2001) have also shown that live Chlamydial elementary bodies (EBs) can have a direct and detrimental effect on sperm physiology whereas heat treatment abolishes the same.…”
Section: Resultsmentioning
confidence: 99%
“…Among bacterial species that interact with spermatozoa are well known causative pathogens of genitourinary infections such as Escherichia coli, Ureaplasma urealyticum, Mycoplasma hominis and Chlamydia trachomatis (Kohn et al, 1998, Hosseinzadeh et al, 2001, Gdoura et al, 2007. E. coli probably represents the most frequently isolated microorganism in genitourinary infections (Weidner et al, 1991).…”
Section: Introductionmentioning
confidence: 99%
“…In vitro experiments have shown that C. trachomatis triggers tyrosine phosphorylation of sperm proteins (Hosseinzadeh et al, 2000), induces premature sperm death (Hosseinzadeh et al, 2001) and stimulates an apoptosis-like response in sperm (Eley et al, 2005b;Satta et al, 2006), leading to increased levels of sperm DNA fragmentation (Gallegos et al, 2008;Satta et al, 2006). At least some of these effects are caused by lipopolysaccharides (Hosseinzadeh et al, 2003).…”
Section: Infertilitymentioning
confidence: 99%